2016
DOI: 10.2337/db16-0680
|View full text |Cite
|
Sign up to set email alerts
|

Improved Glucose Homeostasis in Obese Mice Treated With Resveratrol Is Associated With Alterations in the Gut Microbiome

Abstract: Oral administration of resveratrol is able to improve glucose homeostasis in obese individuals. Herein we show that resveratrol ingestion produces taxonomic and predicted functional changes in the gut microbiome of obese mice. In particular, changes in the gut microbiome were characterized by a decreased relative abundance of Turicibacteraceae, Moryella, Lachnospiraceae, and Akkermansia and an increased relative abundance of Bacteroides and Parabacteroides Moreover, fecal transplantation from healthy resveratr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
143
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(158 citation statements)
references
References 40 publications
14
143
1
Order By: Relevance
“…In this sense, modulation of gut microbiota could be the most remarkable local effect exerted by HT. Recently, another component of the Mediterranean diet, resveratrol, has been shown to modulate positively gut microbiota enhancing glucose tolerance in a mice model of obesity [142] and also through a duodenal Sirt-1 pathway into the hypothalamus [143] enhancing hypothalamic insulin-resistance. Sirt-1 is an energy sensitizer upregulating antioxidative and anti-inflammatory gene expression and improving mitochondrial biogenesis through PGC-1α.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, modulation of gut microbiota could be the most remarkable local effect exerted by HT. Recently, another component of the Mediterranean diet, resveratrol, has been shown to modulate positively gut microbiota enhancing glucose tolerance in a mice model of obesity [142] and also through a duodenal Sirt-1 pathway into the hypothalamus [143] enhancing hypothalamic insulin-resistance. Sirt-1 is an energy sensitizer upregulating antioxidative and anti-inflammatory gene expression and improving mitochondrial biogenesis through PGC-1α.…”
Section: Discussionmentioning
confidence: 99%
“…B). As reported, a lower risk of obesity positively correlated with a larger Bacteroidetes to Firmicutes ratio (Sung et al ., ). These two bacteria were mainly related to energy intake and they have different properties on energy conversion and metabolism (Million et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…As a potent incretin, GLP-1 has been clinically used in the medical management of obese or overweight adults with T2DM. 9,10 Several metabolic pathways, such as amino acid metabolism pathways, energy metabolism pathways, and carbohydrate metabolism pathways, are deregulated in obese mice, whereas the treatment by resveratrol can significantly alleviate these disorders. [5][6][7][8] It has been shown that intestinal flora plays an important role in the control of glucose hemeostasis, while resveratrol was found to be able to maintain the glucose hemeostasis by regulating the balance of intestinal flora.…”
mentioning
confidence: 99%
“…4 The ability of GLP-1 analogues to induce weight loss has been repeatedly demonstrated in several clinical trials studying the weight loss efficacy of a GLP-1 analogue (liraglutide) in nondiabetic obese and overweight individuals. 9 Furthermore, shotgun metagenomics has shown that the glucose-lowering effects of orally administered resveratrol were exerted by significant modification of gut microbial composition and relevant functional pathways. 9,10 Several metabolic pathways, such as amino acid metabolism pathways, energy metabolism pathways, and carbohydrate metabolism pathways, are deregulated in obese mice, whereas the treatment by resveratrol can significantly alleviate these disorders.…”
mentioning
confidence: 99%